Descent for discrete (co)fibrations - Sobral, Manuela (2003)
We characterize the (e ective) E-descent morphisms in the category Cat of small categories, when E is the class of discrete fibrations or the one of discrete co fibrations, and prove that every e ective global-descent morphism is an e ective E-descent morphism while its converse fails.